Surveying the Efficacy of an Open Access Biomedical Informatics Boot Camp - Resendez, Skyler D.; Franklin, Gillian; Tomlin, Crystal; Stephens, Rachel; Maness, Heather; Chamala, Srikar; Koppel, Ross; Elkin, Peter L. (Applied Clinical Informatics, 2025)
This study aimed to assess the efficacy of a biomedical informatics boot camp with regard to improving the skill sets of its participants.The University at Buffalo hosts a free, virtual biomedical informatics boot camp annually. Lectures covering various subject matters are offered, for example, general programming, machine learning, natural language processing, and clinical decision support. Once the 2023 boot camp had concluded, an anonymous voluntary survey was distributed.Seventy percent of the survey respondents indicated that they agreed that their expectations were met. Eighty-two percent of the respondents indicated that our JupyterHub and the associated educational coding materials are useful tools for learning. Free response answers showed a desire for additional hands-on courses over theoretical lectures.The results were overwhelmingly positive. Most respondents felt they had expanded upon their knowledge of informatics. The study also pointed out challenges, including keeping difficulty levels appropriate for an audience with diverse educational backgrounds.
Keywords: education; clinical informatics; consumer health informatics; professional training; informatics specialists